2020
DOI: 10.1186/s40816-020-00202-y
|View full text |Cite
|
Sign up to set email alerts
|

Anti-diabetic effects of pomegranate extracts in long-term high fructose-fat fed rats

Abstract: Background: A high-sugar or/and high-fat diets is a major risk factors for obesity. However, increased fruit and vegetable intake has been recently linked to obesity prevention. The aim of the present study was to investigate the preventive effects of pomegranate leaves (PL), juice (PJ) and peel (PP) extracts, on insulin resistance and oxidative stress in high fat and high fructose diet-induced obese rats. Methods: Obesity in rats was induced by consumption of diet high in saturated fat and fructose (HFD) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 48 publications
(62 reference statements)
1
10
0
1
Order By: Relevance
“…Regarding damage to the body cells i.e beta cells results of our study tally with the previous studies [24][25][26]. Pomegranate's anti-oxidant and anti-diabetic effects observed in this study are in conformity with the previous studies [27,28]. In previous studies it has been found that pomegranate is rich in flavonoids [29].…”
Section: Discussionsupporting
confidence: 91%
“…Regarding damage to the body cells i.e beta cells results of our study tally with the previous studies [24][25][26]. Pomegranate's anti-oxidant and anti-diabetic effects observed in this study are in conformity with the previous studies [27,28]. In previous studies it has been found that pomegranate is rich in flavonoids [29].…”
Section: Discussionsupporting
confidence: 91%
“…between multiple target proteins and a single pathway. These findings imply that the potent pharmacological components of P. granatum may act on these signalling pathways to alleviate the levels of insulin, glucose, inflammation, and oxidative stress associated with diabetes and other related diseases (Amri et al, 2020;Tang et al, 2018).…”
Section: Target Genes and Disease Associa On Networkmentioning
confidence: 92%
“…Due to their improved nutritional value, sensory qualities, improved storage life, and addition of derived components that promote health, fermented fruit beverages serve functional manufacturing needs (Hua et al, 2021). (Amri et al, 2020) shows that leaves, rind, or juice extracts of pomegranate promote decrease insulin sensitivity and promote glycemic control, and limit carbohydrate and lipid absorption by lowering the activities of amylase and lipase. (Andi Alfira et al, 2020) studied In Vitro that the peel powder of fruit Pomegranate had great effect on amylase inhibitor.…”
Section: Introductionmentioning
confidence: 99%